Seeing and Feeling Motion: Canonical Computations in Vision and Touch. - Christopher C Pack; Sliman J Bensmaia (PLoS Biology, 2015)
While the different sensory modalities are sensitive to different stimulus energies, they are often charged with extracting analogous information about the environment. Neural systems may thus have evolved to implement similar algorithms across modalities to extract behaviorally relevant stimulus information, leading to the notion of a canonical computation. In both vision and touch, information about motion is extracted from a spatiotemporal pattern of activation across a sensory sheet (in the retina and in the skin, respectively), a process that has been extensively studied in both modalities. In this essay, we examine the processing of motion information as it ascends the primate visual and somatosensory neuraxes and conclude that similar computations are implemented in the two sensory systems.